The dynamic lives of macrophage and dendritic cell subsets in atherosclerosis. (14th March 2014) - Taghavie‐Moghadam, Parésa L.; Butcher, Matthew J.; Galkina, Elena V.
Abstract : Atherosclerosis, the major pathological process through which arterial plaques are formed, is a dynamic chronic inflammatory disease of large‐ and medium‐sized arteries in which the vasculature, lipid metabolism, and the immune system all play integral roles. Both the innate and adaptive immune systems are involved in the development and progression of atherosclerosis but myeloid cells represent the major component of the burgeoning atherosclerotic plaque. Various myeloid cells, including monocytes, macrophages (MΦs), and dendritic cells (DCs) can be found within the healthy and atherosclerotic arterial wall, where they can contribute to or regulate inflammation. However, the precise behaviors and functions of these cells in situ are still active areas of investigation that continue to yield exciting and surprising new data. Here, we review recent progress in understanding of the complex biology of MΦs and DCs, focusing particularly on the dynamic regulation of these subsets in the arterial wall and novel, emerging functions of these cells during atherogenesis.